Cognitive Behavioral Therapy in Movement Disorders: A Review. Issue 2 (June 2015) - Berardelli, Isabella; Pasquini, Massimo; Roselli, Valentina; Biondi, Massimo; Berardelli, Alfredo; Fabbrini, Giovanni
Abstract: In addition to motor symptoms, patients with movement disorders often complain of psychiatric disturbances, including mood, anxiety, and impulse‐control disorders and psychosis. These abnormalities are often misdiagnosed and left untreated, thus resulting in a worse prognosis and lower quality of life. Besides the use of standard pharmacological treatments, psychiatric abnormalities can be treated by means of nonpharmacological approaches. These approaches include various types of psychological therapies, the most widely used being cognitive behavioral therapy (CBT). We reviewed all articles, conducted until 2014, that contained primary data derived from clinical trials and case reports on the effect of CBT in the most common movement disorders. One randomized, controlled study and several uncontrolled studies on the efficacy of CBT in Parkinson's disease (PD) have shown a short‐term benefit of depression and anxiety. In Tourette's syndrome (TS), CBT has been assessed in a number of large controlled clinical trials that have demonstrated an improvement in psychiatric disturbances and tics. There are no controlled studies on the efficacy of CBT in other types of movement disorders, such as dystonia, Huntington's disease, and essential tremor. Only a limited number of studies have evaluated the efficacy of CBT in the management of psychiatric disorders in movement disorders. The evidence available suggests that CBT is useful in TS and probably useful in PD. We recommend the planning of randomized, controlled clinical trials to investigate the effects of CBT and group CBT in the treatment of psychiatric disturbances in movement disorders.